Desenvolvimento de módulos para habitação popular no Brasil: geração de valor no processo de co-criação com o cliente - Menezes, Marcus Vinicius Cordeiro de (2009)
The market for Brazilian home builders has undergone in recent years trough profound transformations. Changes in supplier-customer relationship has occurred in ways that will affect the suppliers profitability and future market position. This study aimed to evaluate the strategy of co-creation for expansion of the market segment for a Brazilian china and faucets producer. The adoption of this strategy aims to use the company’s intangible assets to increase the added value to their products; to know in detail the reality of the clients and to differentiate itself from competitors in a market with a tendency to commodity. The reassessment of existing strategy, uses as a starting point the core competence and the concepts of innovation and co-creation in order to increase the value perceived by potential customers. To evaluate the results of the strategic repositioning this study will use a non-financial indicator, the Customer Lifetime Value in order to measure the long term impacts.